Non-Coding RNAs and Extracellular Vesicles in Cancer Crosstalk: Diagnostic and Therapeutic Implications (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue, “Non-Coding RNAs and Extracellular Vesicles in Cancer Crosstalk: Diagnostic and Therapeutic Implications”, presents a collection of cutting-edge research articles and reviews that explore the critical roles of non-coding RNAs (ncRNAs) and extracellular vesicles (EVs) in cancer biology. The contributions highlight their diagnostic and therapeutic potential, with particular emphasis on lung and liver cancers. Notable reviews examine the involvement of ncRNAs in airway diseases and their emerging role as liquid biopsy biomarkers for lung cancer. This issue also investigates the role of EV-derived microRNAs (EV-miRNAs) in cancer progression and explores the theranostic potential of Piwi-RNAs contained within extracellular vesicles. Altogether, this collection underscores the promise of ncRNAs and EVs as innovative biomarkers and therapeutic targets, offering a comprehensive overview of recent advances and emphasizing the significance of the ncRNA–EV axis in cancer diagnosis and treatment.